Nadell, Pamela S. and Kate Haulman (Eds.). Making Women’s Histories. Beyond National Perspectives, New York University Press. 2013 - Vásquez, María Gabriela (2017)
Fil: Vásquez, María Gabriela. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras